Weight Change After Subthalamic Nucleus Deep Brain Stimulation in Patients With Isolated Dystonia - He, Weibin; Li, Hongxia; Lai, Yijie; Wu, Yunhao; Wu, Yiwen; Ramirez-Zamora, Adolfo; Yi, Wei; Zhang, Chencheng (Frontiers in Neurology, 2021)
Abstract Purpose: Deep brain stimulation of the subthalamic nucleus (STN-DBS) is an effective treatment method for advanced Parkinson’s disease (PD) and isolated dystonia and provides marked improvement of major motor symptoms. In addition, non-motor effects have been reported including weight gain (WG) in patients with PD after STN-DBS. However, it is still unclear whether patients with isolated dystonia also experience WG. Methods: Data from 47 patients with isolated dystonia who underwent bilateral STN-DBS surgery between October 2012 and June 2019 were retrospectively collected. The severity of dystonia was assessed via the Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS). Changes in the body mass index (BMI) and Burke‐Fahn‐Marsden dystonia rating scale (BFMDRS) score were analyzed using paired Student’s t‐tests. Regression analysis was performed to identify factors that affected the BMI after surgery. Results: Postoperative WG was observed in 78.7% of patients. The percentage of overweight and obese patients increased from 25.5% (before STN-DBS) to 48.9% (at the last follow-up). The mean BMI and mean percentage change in BMI increased by 1.32 ± 1.83 kg/m2 (P<0.001) and 6.28% ± 8.34%, respectively. BMI increased more in female than in male patients. At the last follow-up, BFMDRS movement and disability scores improved by 69.76% ± 33.23% and 65.66% ± 31.41%, respectively (both, P<0.001). The final regression model analysis revealed that sex and preoperative BMI alone were independently associated with BMI change (P<0.05). Conclusions: STN-DBS is associated with postoperative WG with patients with isolated dystonia. WG is more prominent in female patients and is associated with preoperative weight but not with the efficacy of STN-DBS on motor symptoms.